Prohibition on Transforming Agricultural Land from a Benefit Perspective - Aini, Fitrotul; Saleh, Moh (Indonesia Strategic Sustainability, 2025)
Purpose:The differing interests of different parties regarding land often lead to land that should be used for agriculture being converted to other uses. This conversion of agricultural land poses a threat to achieving food security and sovereignty. Methodology:This paper aims to explain the legal rationale for the prohibition on the conversion of sustainable food agricultural land and the beneficial aspects of the prohibition. This research is a normative legal study using both legislative and conceptual approaches.Findings:The results indicate that the legal rationale for the prohibition on the conversion of sustainable food agricultural land aims to achieve food independence, resilience, and sovereignty while simultaneously improving the welfare of farmers, especially those who are vulnerable.Implication:The prohibition on the conversion of sustainable food agricultural land is beneficial in guaranteeing the right to food as a basic human right of every citizen. The government's policy to protect agricultural land sustainably also aims to ensure the fulfillment of all citizens' basic rights related to food needs.